Bottom-up effects on arthropod communities in Platycyamus regnellii (Fabaceae) fertilized with dehydrated sewage sludge - Fernandes de Souza, Gezilene; Leite, Germano Leão Demolin; Silva, Farley William Souza; Sampaio, Regynaldo Arruda; Silva, Júlia Letícia; Texeira, Gustavo Leal; Soares, Marcus Alvarenga; Zanuncio, José Cola (Revista Colombiana de Entomología, 2021)
Sewage sludge is a nitrogen-rich organic compound, which can be used to aid development in plants such as Platycyamus regnellii (Fabaceae), in the recovery of degraded areas. This study aimed to assess the bottom-up effects on leaf mass and percentage of ground cover (leaf litter, herbaceous plants, and grasses) in P. regnellii trees fertilized (or not) with dehydrated sewage sludge and arthropod communities over 24 months. Platycyamus regnellii trees fertilized with dehydrated sewage sludge presented significantly more leaves per branch, branches per tree, and a higher percentage of ground cover compared to unfertilized trees. Phenacoccus sp. (Pseudococcidae) was the most abundant phytophagous insect associated with P. regnellii trees. Fertilization did not affect the abundance, diversity, and species richness of Hemiptera phytophagous on P. regnellii trees. However, fertilized trees presented higher abundance and species richness of trophobiont-tending ants compared to unfertilized trees, with Camponotus sp. being the most abundant regardless of the treatment. Fertilized P. regnellii trees also presented higher species richness of natural enemies compared to unfertilized ones, with Aranae and Dolichopodidae being the most abundant. We concluded that fertilization with dehydrated sewage sludge improved P. regnellii trees leaf mass and ground cover and increased the diversity of trophobiont-tending ants and natural enemies. To our knowledge, this is the first study on the arthropods community associated with this tree species. This suggests that upon fertilization, P. renellii trees are useful for ecological restoration in severely disturbed areas.